2021
DOI: 10.1161/jaha.121.020818
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Interference on Cardiac Implantable Electronic Devices From Apple iPhone MagSafe Technology

Abstract: Background Magnet wireless charging is being utilized increasingly in current generation smartphones. Apple's MagSafe is a proprietary wireless charging technology with an array of magnets that has the capacity to generate magnet fieldstrength >50 gauss (G). We hypothesize that there is clinically significant magnet interference caused by Apple's MagSafe technology on cardiac implantable electronic devices (CIED). Methods and Results This study has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…Our findings are consistent with those by Nadeem et al., 3 who reported a maximum distance of 1.5 cm. The slight difference can be due to the different approach of the ex vivo using the iPhone 12 Pro Max over still‐packaged new devices with respect to our in vitro tests.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with those by Nadeem et al., 3 who reported a maximum distance of 1.5 cm. The slight difference can be due to the different approach of the ex vivo using the iPhone 12 Pro Max over still‐packaged new devices with respect to our in vitro tests.…”
Section: Discussionsupporting
confidence: 94%
“…and Nadeem et al. reported potential risk arising from the static magnetic field due to iPhone 12 MagSafe technology based on ex vivo and in vivo testing on some ICD models 2,3 . Particularly, it was shown that the magnetic mode may be triggered when the iPhone 12 Pro Max is placed directly on the skin over an implantable cardiac device from all three major device manufacturers, and thus, it can inhibit life‐saving therapies 3 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Greenberg et al and Nadeem et al demonstrated inhibition of lifesaving therapies by the Apple iPhone 12 Pro Max. 1 , 2 After these reports were published, the iPhone manufacturer (Apple) released a statement detailing precautionary measures for iPhone users with a cardiac implantable electronic device (CIED) in place. Recommendations were also made to keep the iPhone 12 at a distance of ≥6 in (15 cm) from the CIED as a safety measure to prevent inhibition of lifesaving therapies.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The MagSafe technology, which enables wireless charging functionality, consists of an array of magnets capable of generating a magnetic field of around 0.005 tesla. 2 Studies that have reported interference with implantable devices by the iPhone 12 were not performed on ambulatory patients in a clinical setting. We present a case series of 17 patients with ICDs in whom testing of their device for interference from an iPhone 12 was carried out in an ICD clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nurse tells Mr. Martin that he needs to be careful around common magnets, such as those in newer-generation smartphone chargers, which may interfere with the defibrillator or pacing function when in close contact with the device. He should avoid carrying his phone anywhere near the device, such as in a breast pocket, and should consult with his electrophysiologist about his specific device and smartphone interactions 19. He's also given a device identification card to keep with him in the event he is asked to go through a metal detector.…”
Section: Post-op Care and Potential Complicationsmentioning
confidence: 99%